The Formulation of Carefulness Principle in the Local Regulation of Regional Spatial Order Plan based on Life Environment Sustainability in Maluku Province - I Nyoman Nurjaya Nurjaya (UIN Sunan Kalijaga Yogyakarta, 2014)
The formulation of carefulness principle in the Local Regulation of RegionalSpatial Order Plan based on life environment sustainability in Maluku Province canbe elucidated as follows. First, the formulation of carefulness principle in LocalRegulation of Regional Spatial Order Plan based on life environmentsustainability in Maluku Province has emphasized upon carefulness principlestated in Article 2f UUPPLH and its explanation, and Article 3Government Regulation No. 21 of 2005 and its explanation. Second, theauthor has reformulated Article 52 Verses (3f), (4a), (5c), (6d) and (7a)into Local Regulation of Regional Spatial Order Plan No. 16 of 2013 forMaluku Province.